Future Prospects for Clinical Applications of Nanocarbons Focusing on Carbon Nanotubes. Issue 24 (26th June 2022) - Saito, Naoto; Haniu, Hisao; Aoki, Kaoru; Nishimura, Naoyuki; Uemura, Takeshi
Abstract: Over the past 15 years, numerous studies have been conducted on the use of nanocarbons as biomaterials towards such applications as drug delivery systems, cancer therapy, and regenerative medicine. However, the clinical use of nanocarbons remains elusive, primarily due to short‐ and long‐term safety concerns. It is essential that the biosafety of each therapeutic modality be demonstrated in logical and well‐conducted experiments. Accordingly, the fundamental techniques for assessing nanocarbon biomaterial safety have become more advanced. Optimal controls are being established, nanocarbon dispersal techniques are being refined, the array of biokinetic evaluation methods has increased, and carcinogenicity examinations under strict conditions have been developed. The medical implementation of nanocarbons as a biomaterial is in sight. With a particular focus on carbon nanotubes, these perspectives aim to summarize the contributions to date on nanocarbon applications and biosafety, introduce the recent achievements in evaluation techniques, and clarify the future prospects and systematic introduction of carbon nanomaterials for clinical use through practical yet sophisticated assessment methods. Abstract : Nanocarbons have been applied towards the creation of biomaterials for over 15 years. However, clinical biomaterials employing nanocarbons remain elusive mainly due to concerns of safety. With a particular focus on carbon nanotubes, these perspectives aim to summarize the contributions to date on nanocarbon applications and biosafety evaluation in addition to clarifying the future prospects of clinical nanocarbon applications.